APPLICATION OF ACROBATIC EXEerCI SES IN A HANDBALL TRAINING PROCESS - Radojica Marušić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Ac ro bat exer ci ses re pre sent a ba se for ac qu i ring com plex hand ball exer ci sing techni qu es. Hand ball players get to know dif fe rent types of mo ving and put ting in mo tion dif fe rent parts of body. They ma ster the ba sic com po nents - di rec tion, speed, am pli tu de, in ten sity of ne u ro mu scu lar ten sion, and at the sa me ti me they le arn how to di rect the ir mo tion pre ci sely and how to co or di na te the ir mo ves in spa ce and ti me.